Penerapan Sistem Informasi Perpustakaan Berbasis Web Pada Perpustakaan Umum Rantauprapat - Reyfo Irfankha; Tiara Syavitri Rambe; Marnis Nasution; Angga Putra Juledi; Syaiful Zuhri Harahap (Universitas Labuhanbatu, 2026)
The implementation of a Web-Based Library Information System at the Rantauprapat Public Library aims to increase efficiency and effectiveness in managing library resources. This information system integrates various library functions, such as book cataloging, borrowing, returns, and member management, into a single web-based platform. By using web-based technology, libraries can make access easier for visitors to search for information and borrow online, without being limited by time and place. This research identifies the system's technical and functional requirements and evaluates its impact on library services and visitor satisfaction. The results of implementing this system show an increase in data accuracy, a reduction in service times, and a reduction in administrative errors. Apart from that, this system also makes it easy for visitors to access library information more efficiently. It is hoped that the implementation of this web-based library information system can become a model for other libraries in an effort to improve the quality of library information services in the digital era.